Measurement of B (B→Xsγ), the B→Xsγ photon energy spectrum, and the direct CP asymmetry in B→Xs+dγ decays - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2012)
The photon spectrum in B→Xsγ decay, where Xs is any strange hadronic state, is studied using a data sample of (382.8±4.2)×106 e+e−→Υ(4S)→B¯¯¯B events collected by the BABAR experiment at the PEP-II collider. The spectrum is used to measure the branching fraction B(B→Xsγ)=(3.21±0.15±0.29±0.08)×10−4 and the first, second, and third moments ⟨Eγ⟩=2.267±0.019±0.032±0.003  GeV, ⟨(Eγ−⟨Eγ⟩)2⟩=0.0484±0.0053±0.0077±0.0005  GeV2, and ⟨(Eγ−⟨Eγ⟩)3⟩=−0.0048±0.0011±0.0011±0.0004  GeV3, for the range Eγ>1.8  GeV, where Eγ is the photon energy in the B-meson rest frame. Results are also presented for narrower Eγ ranges. In addition, the direct CP asymmetry ACP(B→Xs+dγ) is measured to be 0.057±0.063. The spectrum itself is also unfolded to the B-meson rest frame; that is the frame in which theoretical predictions for its shape are made.